Complement C7 and clusterin form a complex in circulation - Massri, Mariam; Toonen, Erik J.M.; Sarg, Bettina; Kremser, Leopold; Grasse, Marco; Fleischer, Verena; Torres-Quesada, Omar; Hengst, Ludger; Skjoedt, Mikkel-Ole; Bayarri-Olmos, Rafael; Rosbjerg, Anne; Garred, Peter; et al. (Frontiers in Immunology, 2024)
Introduction The complement system is part of innate immunity and is comprised of an intricate network of proteins that are vital for host defense and host homeostasis. A distinct mechanism by which complement defends against invading pathogens is through the membrane attack complex (MAC), a lytic structure that forms on target surfaces. The MAC is made up of several complement components, and one indispensable component of the MAC is C7. The role of C7 in MAC assembly is well documented, however, inherent characteristics of C7 are yet to be investigated. Methods To shed light on the molecular characteristics of C7, we examined the properties of serum-purified C7 acquired using polyclonal and novel monoclonal antibodies. The properties of serum‑purified C7 were investigated through a series of proteolytic analyses, encompassing Western blot and mass spectrometry. The nature of C7 protein-protein interactions were further examined by a novel enzyme-linked immunosorbent assay (ELISA), as well as size‑exclusion chromatography. Results Protein analyses showcased an association between C7 and clusterin, an inhibitory complement regulator. The distinct association between C7 and clusterin was also demonstrated in serum-purified clusterin. Further assessment revealed that a complex between C7 and clusterin (C7-CLU) was detected. The C7-CLU complex was also identified in healthy serum and plasma donors, highlighting the presence of the complex in circulation. Discussion Clusterin is known to dissociate the MAC structure by binding to polymerized C9, nevertheless, here we show clusterin binding to the native form of a terminal complement protein in vivo. The presented data reveal that C7 exhibits characteristics beyond that of MAC assembly, instigating further investigation of the effector role that the C7-CLU complex plays in the complement cascade.